Molecular type distribution and fluconazole susceptibility of clinical Cryptococcus gattii isolates from South African laboratory-based surveillance, 2005-2013. - Serisha D Naicker; Carolina Firacative; Erika van Schalkwyk; Tsidiso G Maphanga; Juan Monroy-Nieto; Jolene R Bowers; David M Engelthaler; Wieland Meyer; Nelesh P Govender; for GERMS-SA (PLoS Neglected Tropical Diseases)
As is the case globally, Cryptococcus gattii is a less frequent cause of cryptococcosis than Cryptococcus neoformans in South Africa. We performed multilocus sequence typing (MLST) and fluconazole susceptibility testing of 146 isolates randomly selected from 750 South African patients with C. gattii disease identified through enhanced laboratory surveillance, 2005 to 2013. The dominant molecular type was VGIV (101/146, 70%), followed by VGI (40/146, 27%), VGII (3/146, 2%) and VGIII (2/146, 1%). Among the 146 C. gattii isolates, 99 different sequence types (STs) were identified, with ST294 (14/146, 10%) and ST155 (10/146, 7%) being most commonly observed. The fluconazole MIC50 and MIC90 values of 105 (of 146) randomly selected C. gattii isolates were 4 μg/ml and 16 μg/ml, respectively. VGIV isolates had a lower MIC50 value compared to non-VGIV isolates, but these values were within one double-dilution of each other. HIV-seropositive patients had a ten-fold increased adjusted odds of a VGIV infection compared to HIV-seronegative patients, though with small numbers (99/136; 73% vs. 2/10; 20%), the confidence interval (CI) was wide (95% CI: 1.93-55.31, p = 0.006). Whole genome phylogeny of 98 isolates of South Africa's most prevalent molecular type, VGIV, identified that this molecular type is highly diverse, with two interesting clusters of ten and six closely related isolates being identified, respectively. One of these clusters consisted only of patients from the Mpumalanga Province in South Africa, suggesting a similar environmental source. This study contributed new insights into the global population structure of this important human pathogen.